2008
DOI: 10.1002/ptr.2727
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory and antinociceptive activities of gossypin and procumbentin – cyclooxygenase‐2 (COX‐2) inhibition studies

Abstract: In the present study the antiinflammatory and antinociceptive activities of a few selected flavonoids were investigated. Procumbentin, gossypin, chrysin and methylhespiridin were studied for antiinflammatory and antinociceptive activities using in vitro enzymatic assays and in animal models utilizing acetic acid-induced writhing in mice and hind paw edema in rats. In vitro studies were performed using TMPD (NNN'N'-tetramethyl-p-phenylene diamine) and oxygraphic methods for COX-1 (cyclooxygenase-1), COX-2, 5-LO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
1
15
0
2
Order By: Relevance
“…Perception and transmission of pain are complex processes that involve peripheral and central mechanisms. Different mediators, such as 5‐hydroxytryptamine (5‐HT), nitric oxide, prostaglandin, superoxide anion, and cyclooxygenase are involved in pathogenesis of pain . Effective multifaceted pain treatment relies on effective drugs to ensure minimal adverse effects and optimized rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Perception and transmission of pain are complex processes that involve peripheral and central mechanisms. Different mediators, such as 5‐hydroxytryptamine (5‐HT), nitric oxide, prostaglandin, superoxide anion, and cyclooxygenase are involved in pathogenesis of pain . Effective multifaceted pain treatment relies on effective drugs to ensure minimal adverse effects and optimized rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Some compounds such as flavonoids which are well known to display anti-inflammatory and antinociceptive activities 19,20 are common to both studies.…”
Section: Discussionmentioning
confidence: 99%
“…Further in vitro studies also revealed that both procumbentin and gossypin have COX-2 inhibitory activity [26]. In another study, oral administration of flavonoids including gossypin inhibited paw oedema in carrageenin induced oedema in mice [27].…”
Section: Antiinflammatory Activity Of Gossypinmentioning
confidence: 95%